2010
DOI: 10.1016/j.ajog.2010.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of fetal and maternal single nucleotide polymorphisms in candidate genes that predispose to spontaneous preterm labor with intact membranes

Abstract: Objective To determine whether maternal/fetal SNPs in candidate genes are associated with spontaneous preterm labor/delivery. Study Design A genetic association study was conducted in 223 mothers and 179 fetuses [preterm labor with intact membranes who delivered <37 weeks (PTB)], and 599 mothers and 628 fetuses (normal pregnancy): 190 candidate genes and 775 SNPs were studied. Single locus/haplotype association analyses were performed; FDR was used to correct for multiple testing (q*=0.15)]. Results 1) The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 195 publications
(103 reference statements)
1
76
0
3
Order By: Relevance
“…[16][17][18][19][20][21] Genetic factors have also been shown to influence the developing brain's response to sensitizing factors. 22,23 Robust epidemiological studies, performed in preterm and term-born neonates, support a role for inflammation as a sensitizer. These studies suggest a strong association between fetal infection and inflammation (e.g.…”
Section: Concept Of Inflammation-induced Sensitizationmentioning
confidence: 99%
“…[16][17][18][19][20][21] Genetic factors have also been shown to influence the developing brain's response to sensitizing factors. 22,23 Robust epidemiological studies, performed in preterm and term-born neonates, support a role for inflammation as a sensitizer. These studies suggest a strong association between fetal infection and inflammation (e.g.…”
Section: Concept Of Inflammation-induced Sensitizationmentioning
confidence: 99%
“…Furthermore, as only maternal blood samples were available we did not take into account the possible role of fetal genes in our study. A large genetic association study of candidate genes involved in adverse pregnancy outcome has recently accentuated that both maternal and fetal DNA variants are associated with spontaneous preterm delivery [24]. Also, the ideal study genetic study of PTB would take the intricate interactions of environmental factors and genetic predispositions into account.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have traditionally focused on one or a few candidate genes, chosen based on our current understanding of physiology. More recently, genome-wide linkage analyses in families with recurrent PTB and large-scale association studies have revealed further susceptibility genes for PTB [9,21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Некоторые из этих исследований продемонстрировали ассоциацию отдельных генов с преждевременными родами. В част-ности, в американском исследовании были проанализи-рованы 775 одиночных нуклеотидных полиморфизмов в 190 генах-кандидатах, и обнаружилось, что с прежде-временными родами ассоциирован материнский ген -ингибитор металлопротеиназы-2 (Tissue inhibitor of metalloproteinases 2, TIMP2; rs2277698), который регу-лирует ферменты, разрушающие матрикс и метаболизм коллагена IV типа [25]. Этот же ген ассоциирован и с пре-ждевременным разрывом околоплодных оболочек [26].…”
Section: генетическая предрасположенностьunclassified